(untitled) (Journal of Social Sciences Review, 2023)
The digital era has brought a revolution in every field of life and has changed traditional practices strongly. The main purpose of the study was to evaluate the status and challenges of library automation in university libraries of Faisalabad Division, Pakistan. The study used a quantitative research method by following the survey technique to collect data from the entire population. All the university libraries of Faisalabad Division were surveyed, and a total of 15 librarians out of a total of 10 universities responded. The other findings depicted that the university library professionals were taking a minimum salary between 31 thousand to 60 thousand while the maximum was above one Lac rupees. The library automation status showed that all the university libraries were partially automated, and KOHA software was used for automation. The main reason behind the usage of KOHA software was that it was open source self-modified library software. The respondents were overall satisfied with the performance of the software. The respondents were supported by their parent organizations, whereas the annual amount of budget was not sufficient. The respondents of the study agreed with the statements that the library software had the necessary features to automate library functions and were also satisfied with the organization’s financial support to some extent.